Asset Management Using a Web-Based Accounting Online System To Maintain Value of Company Assets - Supriati, Ruli; Aryani, Diah; Maesaroh, Siti (APTISI Transactions on Management (ATM), 2017)
Assets are entities that are tangible or intangible and have economic value. In a company, assets are important, because assets are assets that must be managed properly to provide good benefits also to the company. Companies must be able to keep the value of each company's assets to always be at a high level, avoiding damage so that the value of the asset does not fall in the selling price. With asset management, companies are increasingly eager in planning outgoing expenses to maintain the value of existing assets, monitoring assets that are bought, sold, or otherwise depreciated. Asset management based on this online accounting system, companies get asset data reports, accumulated depreciation of each asset until the asset value is updated or real-time. Any assets that have been added in the system can be archived, edited or deleted. Import feature on this system also facilitate the company in doing penginputan asset data in large quantity. Thus, with the asset management system directly synchronized with the company's financial data, will provide work efficiency in monitoring each company's assets. Keywords​: Asset Management, Real-time, Entities, and Asset Values